Dual synthesis pathways of scaRNA28 via intronic processing of transformation/transcription domain-associated protein transcripts and a novel independent transcription unit - Keiichi Izumikawa; Tatsuya Shida; Hideaki Ishikawa; Sotaro Miyao; Takayuki Ohga; Masato Taoka; Yuko Nobe; Hiroshi Nakayama; Masami Nagahama (RNA Biology)
Small Cajal body-specific RNAs (scaRNAs) are noncoding RNAs involved in the maturation of U-rich small nuclear RNAs. Except for a few that have their own transcription units, most scaRNA genes are embedded in introns and are predicted to be transcribed with host genes. Herein, we report that scaRNA28 is the first scaRNA with a dual synthesis pathway, and that this RNA is transcribed in an independent transcription unit (ITU) by RNA polymerase II while located in intron 2 of the transformation/transcription domain-associated protein (TRRAP) gene. We evaluated the scaRNA28 synthesis pathway using minigenes containing exon 2, intron 2, and exon 3 of TRRAP. A minigene with a mutation preventing 5′ splicing recognition of the exon 2/intron 2 junction generated scaRNA28, suggesting a pathway processing unspliced transcripts into scaRNA28. Even promoterless minigenes and DNA fragments with regions from exons 2 to 3 of TRRAP showed RNA polymerase II-dependent synthesis of scaRNA28, indicating a novel synthesis pathway involving an ITU. Linker-scanning mutational analysis revealed that the promoter region required for scaRNA28 expression in the ITU is located within 60 bases including exon 2/intron 2 junction of TRRAP, and especially the first two bases of intron 2 region, a putative part of the MYC-binding (E-box) motif, are essential for scaRNA28 expression in the ITU. MYC promotes scaRNA28 expression by binding to the promoter region in the ITU. Our findings demonstrated a novel transcriptional pathway for the synthesis of scaRNA28, the first scaRNA with a dual synthesis pathway.